2016
DOI: 10.1371/journal.pone.0162284
|View full text |Cite
|
Sign up to set email alerts
|

Local Hotspots of Endemism or Artifacts of Incorrect Taxonomy? The Status of Microendemic Pill Millipede Species of the Genus Glomeris in Northern Italy (Diplopoda, Glomerida)

Abstract: Local endemic species with their unique evolutionary history always stirred the interest of scientists. One such area especially rich in endemics is northern Italy. In case of pill millipedes of the genus Glomeris Latreille, 1803, only a single species is found in northern Europe, while 22 country-endemics alone are known from Italy. Many of these endemics, however, have not been studied in several decades; therefore we aimed to determine whether this diversity is the result of overlooked synonymies or natural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 34 publications
2
12
0
Order By: Relevance
“…In addition, some other morphological characters used to separate these species by Verhoeff, such as an incomplete second stria on the collum, varies strongly within the here studied G. aurita specimens. Our studies ( Wesener, 2015b ; Wesener & Conrad, 2016 ; this study) confirm that only new collections of these species and subsequent molecular studies will be able to solve the mysteries surroundings the high number of local endemic pill millipedes in northern Italy.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…In addition, some other morphological characters used to separate these species by Verhoeff, such as an incomplete second stria on the collum, varies strongly within the here studied G. aurita specimens. Our studies ( Wesener, 2015b ; Wesener & Conrad, 2016 ; this study) confirm that only new collections of these species and subsequent molecular studies will be able to solve the mysteries surroundings the high number of local endemic pill millipedes in northern Italy.…”
Section: Discussionsupporting
confidence: 67%
“…Given the known isolation of well-researched Monte Baldo during the last Ice Age, it might be possible to date the observed genetic distances of the Monte Baldo population to those of other populations. This dating might allow a more precise dating of the speciation events of the genus Glomeris in northern Italy and beyond to finally gain a better understanding of the pill millipede microendemism so prevalent in the area ( Wesener & Conrad, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In comparison to vertebrate species (e.g., fishes: 0.32 %, Keskin and Atar 2013 or rodents: 2.1 %, Li et al 2015) a maximum intraspecific variation of a p-distance of 5 % is rather high. However, such an intraspecific variation of 5 % was also found in another widespread central European Glomeris , G.klugii/undulata (Wesener and Conrad 2016). A minimum p-distance of 12.9 % of G.marginata to the most closely related species (a factor of 2.6 to the maximum intraspecific p-distance), shows a clear barcoding gap to the nearest congener, G.connexa .…”
Section: Discussionmentioning
confidence: 73%
“…It has been repeatedly demonstrated that DNA sequences provide a powerful tool for the recognition of phylogenetic patterns within a species complex (e.g. [ 1 4 ]) which is essential for the reconstruction of their range evolution (phylogeography) and for defining potential conservation units [ 5 ]. Propelled by an easy DNA data acquisition, this approach has led to a renaissance of its use for taxonomic hypothesis testing in a number of insect species (e.g.…”
Section: Introductionmentioning
confidence: 99%